Diseño de un curso virtual de alfabetización digital para docentes de la Universidad de la Amazonia - Guayara Cuéllar, Cindy Tatiana; Millan Rojas, Edwin Eduardo; Gómez Cano, Carlos Alberto (Revista Científica, 2019)
This article aims to develop a virtual digital literacy course to improve the skills in the use of information and communication technologies (TIC) in teachers of the University of the Amazon of Florence Caquetá. The above with the purpose of proposing a strategy to reinforce digital literacy. The general methodological development was approached from the exploratory and projective methods, using a sample of 100 teachers. To establish the specific methodology was defined: the first phase, diagnosis of the problem, the second phase, the theoretical content and the third phase, designed and implemented the virtual course. The University of the Amazon will have a strategy to address the problem of digital literacy and TIC skills in teachers and at national level may be a reference to implement and improve TIC skills in university teachers.